MEASUREMENT OF COMMUNITY SATISFACTION INDEX HEALTH SERVICES IN TUBAN DISTRICT PUBLIC HEALTH CENTER - Sudrajad, Muhammad; Munir, Miftahul; Enggar, Adibah; Ilmiyah, Surotul (jfpublisher, 2022)
Introduction. To know people's judgment of the services provided by Tuban public health center to the public, there should be a measure of the level of people's satisfaction with health services. The purpose of this study was to measure people's satisfaction based on Permenpan RB number 16 in 2014 and measure people's satisfaction based on the Customer Satisfaction Index (CSIndex). Methods. This study was observational. There were 13 health centers in Tuban analyzed. The sample was 450 people who used health services in Tuban public health centers. The first analysis used the data by Permenpan RB No. 16 of 2014, and the second used the Customer Satisfaction Index (CS Index). Result & Analysis. The results of this research-based Permenpan number 16 of 2014 found all public health centers in Tuban had a value of community satisfaction index in either category. By using CSIndex, it was found that the entire public health center had high satisfaction. Discussion. The value of the Community Satisfaction Index in all public health centers was rather satisfactory. Some reconstruction for supporting facilities, such as clean toilets, comfortable and clean waiting rooms, service information, service flow, management improvement, and product marketing should be done.